Democracy in Social Movements
XIV, 300 p.
Keywords: This collection explores conceptions and practices of democracy of social movement organizations involved in global protest. Focusing on the global justice movement this book shows how they adopt radical new democratic approaches and thus provide a fundamental critique of conventional politics.